2019
DOI: 10.1109/access.2019.2955566
|View full text |Cite
|
Sign up to set email alerts
|

Fast Recognition and Location of Target Fruit Based on Depth Information

Abstract: In order to realize the recognition and localization of the target fruit more accurately and efficiently, an optimized graph-based recognition algorithm based on image depth information is proposed. Firstly, the gradient information of the depth image is obtained from the acquired depth apple image, the gradient vector is reflected from the 3D space to the 2D space, and then rotated 90 degrees clockwise, and the regular region forms the center of the vortex, which is the target fruit center to determine target… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
3

Relationship

3
7

Authors

Journals

citations
Cited by 39 publications
(17 citation statements)
references
References 73 publications
0
17
0
Order By: Relevance
“…Scan the maximum radius of superpixel area where the center of apple is located and fit the target fruit, it is shown in Figure 5. 22 Li used binocular stereo vision technology to obtain the three-dimensional position of the apple and improved the matching accuracy of the two pictures by reducing the search range and the range error was 5%. 23 However, the actual harvesting of the environment is far more complicated than the experimental conditions, the time consumption will obviously increase, and the real-time performance will also be significantly worse.…”
Section: Precise Recognition For Target Fruitmentioning
confidence: 99%
“…Scan the maximum radius of superpixel area where the center of apple is located and fit the target fruit, it is shown in Figure 5. 22 Li used binocular stereo vision technology to obtain the three-dimensional position of the apple and improved the matching accuracy of the two pictures by reducing the search range and the range error was 5%. 23 However, the actual harvesting of the environment is far more complicated than the experimental conditions, the time consumption will obviously increase, and the real-time performance will also be significantly worse.…”
Section: Precise Recognition For Target Fruitmentioning
confidence: 99%
“…The gradient information is obtained from the depth image, and the segmentation algorithm is introduced into the red–green–blue (RGB) image. Finally, the center and maximum radius of the target fruit was scanned to fit the contour size of the target fruit, so as to realize apple recognition and location (Tian et al, 2019 ). Wu proposed a fruit point cloud segmentation algorithm integrating color and three-dimensional geometric features.…”
Section: Introductionmentioning
confidence: 99%
“…The recognition accuracy of green apples reached 88%. Tian [11] proposed a target fruit localization method based on depth image, and located the center and radius of the apple circle respectively through depth image and its corresponding RGB spatial information, so as to fit the target area. Li [12] combined applying saliency detection and Gaussian curve fitting algorithm, a novel algorithm is used to detect green apples in natural scenes, the experimental results indicated that it was effective and feasible.…”
Section: Introduction mentioning
confidence: 99%